Evaluation of neutron flux distribution in structural components and activation products in aluminum alloy at 13-2 channel of the DNRR - Tran , Quoc Duong; Nguyen , Nhi Dien; Nguyen , Kien Cuong; Huynh , Ton Nghiem; Luong , Ba Vien; Nguyen , Minh Tuan; Pham , Quang Huy; Vo , Doan Hai Dang; Do , Minh Phong; Ho , Nguyen Thanh Vinh (Nuclear Science and Technology, 2021)
The estimation of radiological properties of activated structural components of a nuclear reactor due to irradiation of neutron produced by fission is a very important task for radiation safety and reasonable cost of dismantling and radioactive waste management in the decommissioning plan of the reactor. In this work, the calculation approach was carried out by using three-dimensional neutron transport model with the Monte Carlo code MCNP5 to evaluate neutron fluxes and reaction rates. The Bateman equation was solved with neutron absorption reactions (fission and capture) and disintegration by ORIGEN2 code to obtain the activity of materials in reactor structures. This paper presents the evaluation results of the neutron flux distribution and the radioactivity of long-lived key activation products such as 60Co, 55Fe, 59Ni, 63Ni, etc. isotopes in the structural components of the Dalat Nuclear Research Reactor (DNRR). The validation of calculation methodology of the two codes was implemented by comparing calculation results with measured neutron fluxes at irradiation positions in the reactor core as well as specific activities at the bottom part of the aluminum guiding tube at 13-2 channel, which has been removed from the reactor core about six years. The calculation results were in good agreement under 7% difference with the experimental neutron flux value of (6.05±0.52) × 1012 n/cm2.s, and under 33% difference with the experimental specific activities of 60Co isotope being 1.86×104, 9.99×104, and 1.28×105 Bq/g at the positions of -32.5, -17.5 and -2.1 cm (the centerline of the reactor core is at 0 cm), respectively, in the aluminum guiding tube of irradiation channel 13-2. The neutron flux distributions in other structural components such as the graphite reflector, thermal column, thermalizing column, concrete shielding, etc. of the reactor were also evaluated. The obtained calculation results and experimental data are very valuable for the development of a suitable decommissioning plan and a reasonable dismantling strategy for the DNRR.